Estudio de prefactibilidad para la instalación de una planta de preformas biodegradables para botellas con agua - Fernández Villaverde, Cesar Eduardo (2020)
The objective of this research work is to determine the viability of a biodegradable preform production plant for bottles with water, evaluating the economic, technical and financial aspects. Most bottles are made of Polyethylene Terephthalate (PET), this material is polluting when it is incinerated, generating toxic gases; In addition, in natural conditions it can take 1,000 years to degrade. The study proposes that the bottles be made with polylactic acid (PLA), a degradable material in 80 days from vegetable waste. The target market is bottling companies, since preforms are the material they use for the production of their bottles. To determine the projected demand, an interview was conducted with one of the main bottlers: Ajeper S.A. For the location of the plant, a table of confrontation and ranking of factors at the Macro and Micro level was developed determining the location in Lima, Lurin. Plant size is established by analyzing the market, raw material requirement, technology and break-even point. The plant size was determined to be 12,295,619 preforms/year. Regarding the engineering of the project, the production process is similar to PET preforms; therefore, there is the necessary technology, which uses a semi- automatic injection machine. The production capacity of the plant is defined by the bottleneck, which is 27,144 boxes with PLA preforms, in order to determine how much the plant can produce in a given time. The administrative aspect is determined according to the functions that each part of the organization will have. The functions of the collaborators are described and the organization chart of the 19 collaborators is diagrammed. In the project evaluation, an economic NPV of S / .316.371 and a financial NPV of S / .393.023 were obtained.